Pemanfaatan Kulit Kopi Menjadi Teh Cascara - Anis, Ulfah; Yuwana, Yuwana; Syafnil, Syafnil (Universitas Mataram, 2025)
Coffee pulp is typically discarded by local communities without further utilization. In Babakan Bogor, Kepahiang Regency, Bengkulu Province. The coffee pulp has not yet been used productively, primarily due to the community’s limited knowledge and skills regarding coffee by-product processing. The objective of this community service activity was to provide participants with knowledge about the nutritional value of coffee pulp and the processing stages required to produce cascara. The methods employed included (1) preparation through coordination between the community service team and the target audience, and (2) an educational extension approach for material delivery. The implementation of this program was carried out successfully, with a high level of enthusiasm from participants. The activity has contributed to improving the community’s knowledge of coffee by-product utilization, specifically in processing coffee pulp into cascara tea.